Oleanolic Acid Improves Obesity-Related Inflammation and Insulin Resistance by Regulating Macrophages Activation - Li, Wanqing; Zeng, Hongxiang; Xu, Min; Huang, Chenglong; Tao, Linfen; Li, Jun; Zhang, Ting; Chen, Hong; Xia, Jing; Li, Chunli; Li, Xi (Frontiers in Pharmacology, 2021)
The chronic low-grade inflammation of adipose tissues, primarily mediated by adipose tissue macrophages (ATMs), is the key pathogenic link between obesity and metabolic disorders. Oleanolic acid (OA) is a natural triterpenoid possessing anti-diabetic and anti-inflammation effects, but the machinery is poorly understood. This study investigated the detailed mechanisms of OA on adipose tissue inflammation in obese mice. C57BL/6J mice were fed with high-fat diet (HFD) for 12 weeks, then daily intragastric administrated with vehicle, 25mg/kg OA and 50mg/kg OA for 4 weeks. Comparing with vehicle, OA administration in obese mice greatly improved insulin resistance, and reduced adipose tissue hypertrophy, ATM infiltration as well as the M1/M2 ratio. The pro-inflammatory markers were significantly down-regulated by OA in both adipose tissue of obese mice and RAW264.7 macrophages treated with interferon gamma/ lipopolysaccharide (IFN-γ/LPS). Furthermore, it was found that OA suppressed activation of mitogen-activated protein kinase (MAPK) signaling and NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome through decreasing voltage dependent anion channels (VDAC) expression and reactive oxygen species (ROS) production. This is the first report that oleanolic acid exerts its benefits by affecting mitochondrial function and macrophage activation.